ANALISIS KEMAMPUAN LITERASI NUMERASI MAHASISWA DITINJAU DARI GAYA KOGNITIF REFLEKTIF DAN IMPULSIF - Simamora, Ebeneser Wacner; Akhiruddin, Akhiruddin (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2022)
During the Covid-19 pandemic, there was a change in the education system, namely regular or face-to-face Numerical literacy ability is the ability or skill in using various kinds of numbers and symbols related to basic mathematics to solve practical problems in the context of everyday life. This study aims to determine the numeracy literacy ability of students in solving math problems in terms of reflective and impulsive cognitive styles. In looking at students' numeracy literacy skills, indicators of numeracy literacy abilities are used which are adjusted to the stages of the problem solving process. This research is a descriptive research with a qualitative approach. The research subjects consisted of 23 students of the Mathematics Education Study Program at the University of Papua. Data collection consisted of a numeracy literacy test, an MFFT (Matching Familiar Figure Test) test to determine cognitive style, interviews and documentation. The results of the MFFT test showed that there were 11 students with a reflective cognitive style, 9 students with an impulsive cognitive style, 1 student with a low accurate cognitive style, and 2 students with a fast accurate cognitive style. After that, 2 subjects with a reflective cognitive style were obtained which were supported by 2 subjects who had a tendency for a reflective cognitive style and 2 subjects who had an impulsive cognitive style. The results showed that the reflective subject one (SR1) the first reflective student completed the numeracy literacy problem in 91 minutes and the reflective subject two (SR2) completed the problem in 98 minutes, where the two subjects with the minute reflective style had exceeded the predetermined maximum time limit, namely 90 minutes. Impulsive subject one (SI1) completed the numeracy literacy test in 32 minutes. The second impulsive subject (SI2) completed the numeracy literacy test questions within 40 minutes. The two students completed it faster than the specified time limit of 90 minutes. Subjects with a cognitive-reflective style in solving problems take a long time but the results obtained tend to be correct or accurate, while subjects with an impulsive cognitive style seem to be in a hurry to answer and tend to be wrong